2004
DOI: 10.1111/j.1365-3164.2004.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of flea allergy dermatitis: comparison of intradermal testing with flea allergens and a FcɛRI α‐based IgE assay in response to flea control

Abstract: The objective of this study was to evaluate the accuracy of in vivo and in vitro tests in the diagnosis of flea allergy dermatitis in comparison with history, clinical signs and response to flea control. Intradermal testing using four different sources of flea allergens and FcepsilonRIalpha-based immunoglobulin (Ig)E assays were performed in 15 flea-allergic dogs, 15 atopic dogs and 15 dogs infested with fleas but showing no clinical signs of skin disease. Sensitivity, specificity, negative predictive value, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
3
23
0
1
Order By: Relevance
“…By contrast, serological testing was much more sensitive than intradermal testing in that most cats with immediate responses to flea challenge had high IgE titres to flea saliva. A converse result was reported recently in a study that evaluated the serological test and intradermal testing in a group of dogs (Laffort-Dassot et al 2004). …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…By contrast, serological testing was much more sensitive than intradermal testing in that most cats with immediate responses to flea challenge had high IgE titres to flea saliva. A converse result was reported recently in a study that evaluated the serological test and intradermal testing in a group of dogs (Laffort-Dassot et al 2004). …”
Section: Discussionsupporting
confidence: 52%
“…Based on the results of this study, there is a strong likelihood of false-negative reactions, although the specificities obtained in the present studies suggest that a false-positive reaction is quite unlikely. The frequent discordance of results obtained with the three commercial allergens assessed may reflect a lack of standardisation and variability in the composition and concentration of the extracts (Laffort- Dassot et al 2004). By contrast, serological testing was much more sensitive than intradermal testing in that most cats with immediate responses to flea challenge had high IgE titres to flea saliva.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, we should have monitored sensitizing IgE irrespective of the possibility that there might be non-sensitizing IgE allotypes in cats. Likewise, some studies on humans and dogs have demonstrated considerable variation in the correlation of allergen-specific serum IgE antibodies with allergen-induced immediate type reactions (Foster et al 2003;Foster and O'Dair 1993;Laffort-Dassot et al 2004;Purohit et al 2005), whereas other studies on cats and dogs have shown significant agreement between serological and biological assays (McCall et al 1997;Stedman et al 2001). Since methods and reagents used in the various studies were different, it is difficult to compare the results of the various studies.…”
Section: Discussionmentioning
confidence: 94%
“…However, studies that compared serological tests with skin tests to document allergic sensitization in dogs, cats, and humans have shown that levels of free, allergenspecific immunoglobulin in serum are not always associated with skin reactions based on allergen-specific antibodies bound to allergic effector cells (Foster and O'Dair 1993;Jackson et al 1996;Gilbert and Halliwell 1998;Laffort-Dassot et al 2004;Purohit et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Intradermal testing is the standard method for identifying IgE-mediated allergic reaction in vivo , but it requires specific equipment and manipulation in each veterinary clinic (Laffort-Dassot et al , 2004). At the opposite, specific serum IgE measurement can be performed in a well-equipped laboratory and requires only a blood sample at the veterinary clinic level.…”
mentioning
confidence: 99%